Digital transformation in the Islamic economy: Innovations and challenges in 2025 - Muflih Adi Laksono; Rahmat Setiawan; Nurhasanah Pasaribu (Journal of Islamic Economy, 2025)
This study aims to examine the role of digital transformation in supporting the development of the sharia economy, especially in terms of technological innovation and the challenges of its implementation until 2025. Digital transformation is considered an important element in driving operational efficiency, expanding financial inclusion, and strengthening the sustainability of an economic system based on Islamic values. This study uses the Systematic Literature Review (SLR) method, which is a systematic and structured approach to identifying, evaluating, and analyzing relevant scientific literature. The SLR process includes formulating research questions, determining inclusion and exclusion criteria, selecting databases such as Scopus, Google Scholar, and ScienceDirect, and thematic analysis of the results of the literature review. The results of the study show that various digital innovations such as sharia fintech, blockchain, and artificial intelligence (AI) have made significant contributions to increasing the efficiency and transparency of sharia financial services. However, this digitalization also presents a number of challenges such as unpreparedness of regulations, minimal technological fatwas, and low sharia digital literacy among the public. Therefore, collaboration between regulators, practitioners, academics, and scholars is needed to build a digital sharia economic ecosystem that is inclusive, safe, and in accordance with the principles of maqashid sharia